Expropriation of Minority Shareholders' Rights: Evidence from Malaysia - Nurul Huda, Mustafa (2011)
This paper examines the extent level of expropriation of minority shareholders' rights in Malaysia. The study aims to investigate whether the following variables influence the expropriation of minority shareholders' rights in Malaysia. Analysis of 60 companies listed from two industries in Bursa Malaysia was selected. Descriptive analysis and ordinary least squares (OLS) regression model are performed in this study. From six variables that are tested only three variables can be concluded as factors influencing the expropriation of minority shareholders' rights in Malaysia. The number of independent outside directors increases the potential for expropriation of minority shareholders' rights. However, this relationship became opposite when the directors have a different characteristic among boards that affect their independence level. Profitability and growth are highly correlated. When the model is estimated using either one of them, the result is significantly negative, which means that profitable or growing firms have less incentives to engage in related party transactions (RPT). Ownership concentration, level of leverage and size are not significant in explaining the level of expropriation of minority shareholders in RPT.